2018
DOI: 10.1186/s12931-018-0810-3
|View full text |Cite
|
Sign up to set email alerts
|

A home monitoring program including real-time wireless home spirometry in idiopathic pulmonary fibrosis: a pilot study on experiences and barriers

Abstract: In idiopathic pulmonary fibrosis (IPF), home monitoring experiences are limited, not yet real-time available nor implemented in daily care. We evaluated feasibility and potential barriers of a new home monitoring program with real-time wireless home spirometry in IPF. Ten patients with IPF were asked to test this home monitoring program, including daily home spirometry, for four weeks. Measurements of home and hospital spirometry showed good agreement. All patients considered real-time wireless spirometry usef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
77
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(90 citation statements)
references
References 9 publications
12
77
1
Order By: Relevance
“…The authors of this study identified a diurnal variation with higher FVC values in the morning compared to the afternoon. In line with our observations, two other studies described FVC variability of 0.04 to 0.39 L over 28 days of home spirometry in patients with IPF [ 12 , 28 ]. Indeed, these analyses were only used to evaluate within-subject reproducibility of measurements and were not analysed for their correlation with disease progression [ 12 , 28 ].…”
Section: Discussionsupporting
confidence: 93%
“…The authors of this study identified a diurnal variation with higher FVC values in the morning compared to the afternoon. In line with our observations, two other studies described FVC variability of 0.04 to 0.39 L over 28 days of home spirometry in patients with IPF [ 12 , 28 ]. Indeed, these analyses were only used to evaluate within-subject reproducibility of measurements and were not analysed for their correlation with disease progression [ 12 , 28 ].…”
Section: Discussionsupporting
confidence: 93%
“…Co-development of home monitoring systems with patients might lead to higher adherence and patient satisfaction with home monitoring. 8 , 9 The identified statistical analysis challenges could be tackled by predefining the minimum number of measurements that are needed for reliable longitudinal analysis, and unifying the way that missing data and outliers are handled.…”
mentioning
confidence: 99%
“…On the other hand, ILD specialists need to better interact The main symptoms that drive QoL in IPF are cough, dyspnoea and anxiety 28 . Different treatment strategies have been used to relieve chronic cough and progressive dyspnoea associated with pulmonary fibrosis, presenting limited evidence and modest results 29,[40][41][42][43][44][45][46][47] .…”
Section: Palliation Of Symptomsmentioning
confidence: 99%
“…Finally, increasing shortness of breath and immobility in advanced stages represent another challenge for many patients and create problems in accessing healthcare. New home care programs that incorporate eHealth technologies hold vast potential for facilitating real-time data about patient situation and requirements 41,50 . Therefore, the ILD community should work to find better options for symptom palliation from initial stages of the disease and also to set the best healthcare strategy for patient acceptance and participation in care.…”
Section: Palliation Of Symptomsmentioning
confidence: 99%